Stock status of skipjack tuna (Katsuwonus pelamis Linnaeus, 1758) using length-based assessment in Cenderawasih Bay, Indonesia - Nurdin, Erfind; Taufik, Muhammad; Lestari, Pratiwi; Ma’mun, Asep; Kembaren, Duranta D.; Tirtadanu,; Noegroho, Tegoeh; Prihatiningsih,; Panggabean, Anthony S. (Penerbit Universiti Kebangsaan Malaysia, 2025)
The West Pacific and the waters of Cenderawasih Bay are potential fishing grounds and part of the fishery management area (FMA) 717 of the Republic of Indonesia. Increased production demand may result in overfishing, which has led to the depletion of fish stocks. To ensure the long-term viability of these fisheries, effective management practices are essential. This study aims to examine size distribution, growth, and population parameters that can be used as fish resource management inputs for skipjack fisheries in Cenderawasih Bay. Length-based approach was used to estimate biological parameters and the dynamics of populations as well as the stock status within data-limited fisheries. Length frequency data was used to assess the Katsuwonus pelamis fisheries condition. From January to November 2021, in all of 2,211 fish were taken samples from numerous commercial small-scale vessel units that were operating around anchor fish aggregating devices (FADs). The results showed that the exploitation rate (E) was 0.69 year1, L∞ = 96.8 cm fork length (cmFL), k= 0.38 year-1, and t0 = -0.31 year. Natural mortality (M) was 0.66 year-1, fishing mortality (F) was 1.46 year-1, and total mortality (Z) was 2.12 year-1. Overfishing condition has occurred according to the current fishing mortality rate (Fcur=1.46 year-1), which has exceeded the reference point of maximum fishing mortality (Fmax =0.76 year-1) and F40% (0.9 year-1). The growth overfishing condition was indicated based on the current selectivity of handline (Lccur=42 cm), which is smaller than the optimal selectivity of Lmax (55 cm). Some management tools, such as the regulation on minimum size of hooks and the total allowable catch (TAC) system, can be utilized to consider skipjack tuna fisheries sustainability in Cendrawasih Bay.